ANALISIS SISTEM PADA PENGGAJIAN DI PT APLUS PASIFIC - Nurdiyanto Yusuf (Asosiasi Dosen Muda Indonesia, 2023)
To find out whether a company is a company that has a good and correct system, a control system is needed that can make the company more thorough and have more specific and good payroll data. The internal control system is one of theÂ information systems implemented by the company in achieving its goals. his company. In realizing a good and appropriate company system, an analysis and evaluation is needed. Where this is expected to be able to prevent fraud that can occur within a company. The analytical method used is a Flowchart, which is an analytical technique used to describe several aspects of an information system in a clear, concise and logical manner. Flowcharts use standard symbols to describe through pictures the transaction processing procedures used by the company and the flow of data through the system. The benefit of this system is to help clarify complex processes in the decision-making process. The conclusions obtained from the PayrollÂ Information System Analysis, the company seeks to carry out theÂ function properly. However, the company has not implemented a payroll information system that is more complex so that it can cause errors in the payroll system within the company.